Pediatric healthcare service utilization after the end of COVID-19 state of emergency in Northern Italy: a 6-year quasi-experimental study using interrupted time-series analysis - Puntoni, Matteo; Caminiti, Caterina; Maglietta, Giuseppe; Lanari, Marcello; Biasucci, Giacomo; Suppiej, Agnese; Marchetti, Federico; De Fanti, Alessandro; Caramelli, Fabio; Iughetti, Lorenzo; Ghizzi, Chiara; Valletta, Enrico; et al. (Frontiers in Public Health, 2025)
BackgroundEvidence exists on the major disruptions in pediatric healthcare services occurred during the COVID-19 pandemic, but what happened when all restrictions were lifted is unclear. This study examined trends in pediatric hospital admission and Emergency Department visit rates during the first 12 months following the end of the state of emergency in Italy, compared to pre-pandemic levels.MethodsWe conducted a multicenter, retrospective, quasi-experimental before after study including 11 North Italian hospitals. Using electronic health records from March 2017 to March 2023, we compared standardized rates recorded during 1 year following the end of the emergency with the situation before the pandemic, using interrupted time series. We examined trends overall and for individual diagnostic categories that had exhibited the largest impact in our previous studies concerning data up to March 2022.ResultsA total of 104,083 hospitalizations and 858,762 Pediatric Emergency Department visits were analyzed. Compared to the 3 years before the outbreak, post-emergency hospitalization rates increased by 23% (Standardized Hospitalization Rate Ratio 1.23, 95% CI 1.20–1.25), whereas Pediatric Emergency Department visits after a sharp decrease returned to pre-pandemic rates (Standardized Incidence Rate Ratio 0.98, 95% CI 0.96–1.00). Mental health-related hospitalizations exhibited the largest increase, peaking in the first months of the post-pandemic year (level change, Hospitalization Rate Ratio (HRR)2.57, 95%CI 1.61–4.12), then decreasing slightly in the last months but still maintaining much higher than pre-pandemic values. Notably, hospitalization rates in adolescent girls (12–17 years) increased almost 4-fold (level change, HRR 3.72, 95%CI 2.02–6.85, p < 0.001), whereas the increase was not significant for boys in the same age group (level change, HRR 1.42, 95%CI 0.65–3.11, p = 0.378). Respiratory diseases, after drastically declining during the two pandemic years, experienced steadily increasing monthly trends, finally stabilizing in the post-pandemic year at pre-pandemic levels.ConclusionThe COVID-19 pandemic has had long-term consequences on pediatric healthcare utilization. Data from this and future studies can guide the development of proactive policies aiming to mitigate healthcare disruptions and ensure access to essential pediatric services in the event of future health crises, with special consideration to vulnerable populations. The persistent rise in hospital admissions for mental health disorders, particularly teenage girls, make this field a challenging, absolute priority for public health.